2021
DOI: 10.3892/or.2021.7920
|View full text |Cite
|
Sign up to set email alerts
|

CDCA5 promotes the progression of prostate cancer by affecting the ERK signalling pathway

Abstract: Cell division cycle-associated 5 (CDCA5) can regulate cell cycle-related proteins to promote the proliferation of cancer cells. The purpose of the present study was to investigate the expression level of CDCA5 in prostate cancer (PCa) and its effect on PCa progression. The signalling pathway by which CDCA5 functions through was also attempted to elucidate. Clinical specimens of PCa patients were collected from the Second Hospital of Tianjin Medical University. The expression level of CDCA5 in cancer tissues an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 40 publications
(50 reference statements)
1
12
0
Order By: Relevance
“…Nonetheless, this study also showed that high CDCA5 expression was significantly associated with an increase in cell cycle activity markers such as Ki67 and Cyclin B1. This in consistent with a previous study by Ji et al, which indicated that high CDCA5 expression is associated with poor survival in prostate cancer [ 45 ] Furthermore, our functional results suggest that decreasing CDCA5 occurs with an accumulation of cells in the G2/M phase of cell cycle in aggressive tumors. This may be explained by pro-oncogenic role of CDCA5 during the cell cycle that impairs cancer apoptosis while promoting cell proliferation via the PI3K/AKT/mTOR signalling pathway, which was shown on our results at transcriptomic level.…”
Section: Discussionsupporting
confidence: 93%
“…Nonetheless, this study also showed that high CDCA5 expression was significantly associated with an increase in cell cycle activity markers such as Ki67 and Cyclin B1. This in consistent with a previous study by Ji et al, which indicated that high CDCA5 expression is associated with poor survival in prostate cancer [ 45 ] Furthermore, our functional results suggest that decreasing CDCA5 occurs with an accumulation of cells in the G2/M phase of cell cycle in aggressive tumors. This may be explained by pro-oncogenic role of CDCA5 during the cell cycle that impairs cancer apoptosis while promoting cell proliferation via the PI3K/AKT/mTOR signalling pathway, which was shown on our results at transcriptomic level.…”
Section: Discussionsupporting
confidence: 93%
“…Abnormal cell division can lead to cancer. Disturbance of cell cycle regulation is an important biological feature exhibited in malignant tumors and can lead to reduced apoptosis, unlimited proliferation and metastasis in malignant cells (30). CDCA3 belongs to a family of cell division-associated proteins, which function as part of the SKP1-Cullin-RING-F-box ubiquitin ligase complex that mediates the destruction of the mitosis-inhibitory kinase wee1 (14,16).…”
Section: Discussionmentioning
confidence: 99%
“…There is now growing evidence that CDCA5 is overexpressed as an oncogene in a variety of common malignancies and has been proven to play a crucial part in tumorigenesis and development, including NSCLC, 13 hepatocellular carcinoma, 14 , 15 prostate cancer, 16 , 17 gastric cancer, 18 , 19 ovarian cancer, 20 nasopharyngeal carcinoma, 21 bladder cancer, 22 esophageal squamous cell carcinoma, 23 colorectal cancer, 24 breast cancer, 25 oral squamous cell carcinoma. 26 So far, only Nguyen et al have discussed the relationship between CDCA5 and NSCLC in detail, and they reported that CDCA5, recognized as an independent prognostic factor of NSCLC, played an essential role in the growth of lung cancer cells.…”
Section: Introductionmentioning
confidence: 99%